2006
DOI: 10.1538/expanim.55.457
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Pre- and Post-Surgery Treatment with Risedronate on Trabecular Bone Loss in Ovariectomized Rats

Abstract: The purposes of the present study were to differentiate the effects of pre-surgery treatment with risedronate and post-surgery treatment with a reduced dosing frequency of risedronate on trabecular bone loss in ovariectomized rats and to determine whether postsurgery treatment with a reduced dosing frequency of risedronate would have a beneficial effect on trabecular bone loss after pre-surgery treatment Materials and Methods Treatment of animalsOne hundred female Sprague-Dawley rats, 3 months of age, were pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
(17 reference statements)
1
1
0
Order By: Relevance
“…In the present study, 7 days after ovariectomy no differences in body weight were observed between groups as previously reported [49]. An increase in body weight in OVX mice was observed at the end of the experiments.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, 7 days after ovariectomy no differences in body weight were observed between groups as previously reported [49]. An increase in body weight in OVX mice was observed at the end of the experiments.…”
Section: Discussionsupporting
confidence: 90%
“…A second group (6/time point) received an OVX and was assigned to 2, 6, or 12 week time points. Statistical power analysis was conducted a priori, based on literature data from sham and OVX Sprague–Dawley rats (bone volume fraction: BV/TV = 0.18 ± 0.04 for sham and 0.06 ± 0.02 for OVX at 10 weeks post‐OVX). A difference in BV/TV of 0.06 (one half the 0.12 difference between the sham and OVX groups) between groups could be detected with a power of 90% with a p = 0.05.…”
Section: Methodsmentioning
confidence: 99%